The Effect of Experimental Methods on Student Learning Outcomes in Science Subjects Material Changes in Energy at Madrasah Ibtidaiyah: Pengaruh Metode Eksperimen Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA Materi Perubahan Energi di Madrasah Ibtidaiyah - Riza Dia Utari Matroji; Ida Rindaningsih (Universitas Muhammadiyah Sidoarjo, 2022)
This study investigates the impact of an experimental method on student learning outcomes in science lessons focusing on energy change at MI Ma'arif Sentul. Using a quantitative experimental approach, the research demonstrates that the experimental method significantly enhances student learning outcomes. The findings indicate increased engagement and enthusiasm, making the learning process more enjoyable and preventing monotony. The experimental method influences student learning outcomes by approximately 26.6%, as measured by the N-Gain test. Overall, this study highlights the effectiveness of the experimental method in improving science education. Highlights: Experimental method enhances learning outcomes: The study demonstrates that the experimental method employed in science lessons on energy change at MI Ma'arif Sentul positively influences student learning outcomes. Increased engagement and enthusiasm: The use of the experimental method makes the learning process more enjoyable and prevents monotony, leading to improved student engagement and enthusiasm for learning. Significant effect and moderate impact: The experimental method has a statistically significant effect on student learning outcomes, as evidenced by the t-test results. Moreover, the N-Gain test shows a moderate impact of approximately 26.6% on learning outcomes Keywords: experimental method, learning outcomes, energy change, science lessons, students.